Sustainable mortars for rehabilitation of old plasters. (15th December 2016) - Torres, Isabel; Matias, Gina
Highlights: Research about the viability of introduction of ceramic residues into lime mortars. Some properties of the raw materials used are analyzed. Characterization of hydraulic lime mortars with red and white clay ceramics. Results encourage the development of new sustainable solutions for mortars. Abstract: External coatings of walls are the most exposed construction elements, and, consequently, the first ones needing maintenance, repair, rehabilitation or replacement. When old heritage buildings are considered, we must bear in mind not only the functional aspects of the coatings but also the preservation of its history. Having regard to this conditioning and the degradation of a wall covering, the first option should always be its conservation, maintenance and repair. Total replacement should only be considered as a last resort. In that case, there are two possible solutions: the reproduction of the old mortar or the production of a compatible one. Following exclusively and strictly one of the indicated ways is not viable, and so an integrated methodology must be adopted: the composition of the existing mortar must be taken into account and all of its constituents (amounts and types) must be as similar as possible. Also, the most significant functional characteristics must be reproduced. In ancient times, in the absence of natural pozzolans, ceramic milled residues were frequently used as artificial pozzolans and also as aggregates, providing some hydraulicity and durability to lime mortars. This paper presents some findings of an extensive research carried out at the University of Coimbra in which the viability of the introduction of ceramic residues into lime mortars is analysed. Some properties of the raw materials used for mortars production are analysed. Also, the results obtained in the mechanical characterization of hydraulic lime mortars with red and white clay ceramics are presented. The presented characterization provided some promising results, encouraging the development of new sustainable solutions for mortars production.